2011
DOI: 10.1590/s0365-05962011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico dos pacientes com vitiligo e sua associação com doenças da tireoide

Abstract: BACKGROUND: Vitiligo is considered the most frequent acquired hypomelanosis. Although its pathogenesis is uncertain, it is believed that autoimmune etiology is the most plausible. This theory is based on the coexistence of vitiligo with autoimmune diseases. Objectives: To describe the epidemiological profile of vitiligo patients and to estimate the prevalence of the association of vitiligo with autoimmune thyroid diseases. Methods: A cross-sectional study was conducted through analysis of the medical records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 24 publications
(45 reference statements)
3
21
0
5
Order By: Relevance
“…Results of more recent studies on the association between vitiligo and disorders of the thyroid gland are reported in table 4 [6,7,9,10,12,16,17,18,23,24,28,33,34,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. Most surveys involving a control group showed a significant statistical difference in the prevalence of thyroid gland disorders between vitiligo patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of more recent studies on the association between vitiligo and disorders of the thyroid gland are reported in table 4 [6,7,9,10,12,16,17,18,23,24,28,33,34,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. Most surveys involving a control group showed a significant statistical difference in the prevalence of thyroid gland disorders between vitiligo patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in agreement with the results of our multivariate analysis. Nunes and Esser [41] showed an association between circulating anti-TPO antibodies and late onset of vitiligo. In the multivariate analysis, no association between the presence of circulating anti-TPO antibodies and late onset or clinical subtypes of vitiligo was shown in our sample; this observation is in agreement with the report of Daneshpazhooh et al [39], but not with the data published by Kasumagic-Halilovic et al [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors attributed this at least in part to higher rates of consanguinity in the Turkish population. The prevalence of thyroid disorders in Brazil, which has a more diverse ethnic population, is lower at 22% [3]. In Asian countries such as Japan [4] and India, the rates of comorbid autoimmune disease are even lower, with several studies from India [5,6,7] showing anywhere from 3% to 11% of vitiligo patients having another autoimmune condition.…”
Section: Introductionmentioning
confidence: 99%
“…У пациентов с витилиго, по данным D. Nunes и соавт. [30], повышенный уровень анти-тел к ткани щитовидной железы определяется в 32,8% случаев. Нарушение функции щитовидной железы (клиническое и субклиническое) зареги-стрировано у 22,4% пациентов, из них в 80% -гипо-тиреоз, в 13,3% -тиреотоксикоз, в 6,7% -субкли-нический гипотиреоз.…”
unclassified